2019
DOI: 10.5194/tc-13-2421-2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating snow depth on Arctic sea ice using satellite microwave radiometry and a neural network

Abstract: Snow lying on top of sea ice plays an important role in the radiation budget because of its high albedo and the Arctic freshwater budget, and it influences the Arctic climate: it is a fundamental climate variable. Importantly, accurate snow depth products are required to convert satellite altimeter measurements of ice freeboard to sea ice thickness (SIT). Due to the harsh environment and challenging accessibility, in situ measurements of snow depth are sparse. The quasi-synoptic frequent repeat coverage provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 35 publications
(123 reference statements)
1
13
0
Order By: Relevance
“…The snow depth over sea ice was estimated with an RMSE of 5.1 cm, using a multilinear regression with the TBs at 6, 18, and 36 GHz on vertical channels. Braakmann-Folgmann and Donlon [28] proposed an artificial neural network using both AMSR2 and Soil Moisture and Ocean Salinity (SMOS) data as input to retrieve snow depths in the Arctic in 2019. Trained using seven years of OIB snow depth data, the algorithm is suitable for FYI and MYI, and the bias and the RMSE relative to OIB snow depth data were 1.1 and 4 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The snow depth over sea ice was estimated with an RMSE of 5.1 cm, using a multilinear regression with the TBs at 6, 18, and 36 GHz on vertical channels. Braakmann-Folgmann and Donlon [28] proposed an artificial neural network using both AMSR2 and Soil Moisture and Ocean Salinity (SMOS) data as input to retrieve snow depths in the Arctic in 2019. Trained using seven years of OIB snow depth data, the algorithm is suitable for FYI and MYI, and the bias and the RMSE relative to OIB snow depth data were 1.1 and 4 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The topographical information such as snow cover area is one of the most important variables for the application of hydrological model [18][19][20], and can dominate local and regional climate, and hydrology. Snow and glacier strongly influence the regional radiation budget with its high albedo and acts as an insulation, controlling snow accumulation and melt [21]. In this regard, accurate representation of snow cover at micro-scale of spatial variation is required to provide accurate and timely information on water availability and its management.…”
Section: Introductionmentioning
confidence: 99%
“…We plan to apply our ensemble-based deep neural network to the AMSR-E and AMSR2 to examine to what extent the snow depth retrieval can be improved by considering lower frequency brightness temperatures. More recently, Braakmann-Folgmann and Donlon [53] attempted to retrieve snow depth over sea ice using a multi-source of satellite microwave radiometer measurements with a neural network. They showed that the inclusion of the L-band of SMOS as the additional input could lead to better estimation of snow depth.…”
Section: Discussionmentioning
confidence: 99%
“…Each hidden layer contains a number of neurons that allow the network to learn more complicated, non-linear relationships between multi-frequencies (channels) microwave emissions from within a snow layer and snow depth, i.e., the neurons in the first hidden layer make simple decisions, and then the neurons in the second hidden layer make more complicated decisions than those in the first hidden layer. More recently, Braakmann-Folgmann and Donlon [53] attempted to retrieve snow depth over sea ice a deep neural network using a gradient ratio of selected frequencies of brightness temperatures as the input and showed promising results. However, a specific network shows certain sensitive dependence on initially assigned weight and bias to the neurons.…”
Section: Introductionmentioning
confidence: 99%